2007
DOI: 10.1038/sj.jid.5700739
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin Mutations in Children with Severe Atopic Dermatitis

Abstract: Atopic dermatitis (AD) results from strong genetic and environmental interactions. AD shows genetic linkage to Chromosome 1q21. This region contains the epidermal differentiation complex (EDC), which consists of genes that form essential components of epidermal surfaces. Filaggrin (FLG) is one of these. Mutations in FLG/(R501X and 2282del4) are reported to be strongly associated with AD and to influence asthma accompanying AD. We investigated these effects in families recruited through a child with severe AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
152
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(170 citation statements)
references
References 40 publications
12
152
1
5
Order By: Relevance
“…A number of studies have been conducted to replicate the original findings, and some have confirmed and others refuted the association of FLG with AD (Marenholz et al 2006;Ruether et al 2006;Weidinger et al 2006Weidinger et al , 2007Barker et al 2007;Morar et al 2007;Stemmler et al 2007). To examine the association of common FLG variants with AD development, we performed tSNP analysis of Japanese AD families and case-control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been conducted to replicate the original findings, and some have confirmed and others refuted the association of FLG with AD (Marenholz et al 2006;Ruether et al 2006;Weidinger et al 2006Weidinger et al , 2007Barker et al 2007;Morar et al 2007;Stemmler et al 2007). To examine the association of common FLG variants with AD development, we performed tSNP analysis of Japanese AD families and case-control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of AD patients do not carry FLG. In children, FLG accounts for only 26.7% of the patients with AD, suggesting that other skin barrier genes, particularly those in the epidermal differentiation complex of chromosome 1q21, likely exist to account for the barrier defects in AD patients without FLG (10,11). Abnormalities in skin lipid composition (6), excessive serine protease activity (as illustrated by the ichthyosiform disease Netherton syndrome, which is caused by mutations in SPINK5 that encodes for lymphoepithelial Kazal-type-related inhibitor) (6), claudins of tight junction (12), or suppression of skin barrier protein expression by inflammation (9) may constitute other causes of skin barrier defects in AD.…”
Section: Filaggrin Mutations: Evidence For Physical Barrier Defects Amentioning
confidence: 99%
“…These genetic mutations, previously proven to impair the formation of stratum corneum (5), strongly predispose to childhood eczema in several white European populations, where these mutations are prevalent (3,(6)(7)(8)(9)(10)(11), including Scottish, English, Irish, Danish and German populations. Analogous mutations leading to loss of function have Background: Filaggrin (FLG) null mutations are important genetic predisposing factors for atopic asthma and have recently been shown to influence controller and reliever medication needs in asthmatic children.…”
mentioning
confidence: 99%